Lucian Blaga și corespondenții săi germani (II) - Mihaela Pappu (Revista de Istorie și Teorie Literară)
The text presents the German correspondence of Lucian Blaga, found in the Blaga Fund of the National Museum of Romanian Literature. This correspondence was not turned to account until the present days; it proves to be viable from historical and literary point of view, not only for Blaga’s biobibliography, but also for the historiography of the multiculture professed in the inter-war period; generally it can constitute itself in a documentary source, also for the evolution of mentalities, as well as for the Romanian imagology.